Evaluation of the Lectin Pathway in the Serum of Patients with Chronic Chagas Disease by Detection of C4 by Elisa - Renan Polachini; Lorena Bavia; Fabiana A. Andrade; Kárita C. F. Lidani; Vanessa F. Picceli; Nathalia M. D. L. Signorini; Pâmela D. Fontana; Helena M. B. S. Plácido; Iara J. M. Reason (Sociedade Brasileira de Patologia Clínica, 2022)
ABSTRACT Chagas disease (CD) is a chronic tropical disease caused by Trypanosoma cruzi , affecting about 8 million people in Latin America. The lectin pathway (LP) of the complement system is one of the first lines of host defense in the response against T. cruzi , and can continue to be activated in chronic infection due to the escape of the parasite to its action. Although some components of this pathway have been investigated in CD, there are no reports on its activation in patient serum. In this context, our objective was to evaluate the activation of LP in chronic chagasic patients and controls by the detection of the C4 component, using the direct ELISA assay. For this purpose, serum of 80 patient with chronic CD (clinical forms: asymptomatic n=17; symptomatic n=63; cardiac n=45; cardio digestive n=13; digestive n=5) followed at the Ambulatory of Attention to Chagasic Patients (HC/UFPR) and 80 healthy controls (donors of the Blood Bank of HC) were evaluated regarding the evaluation of the LP. The results showed that LP activation by mannose-binding lectin (MBL) was found reduced while activation by ficolins was increased in patients with CD when compared to controls. The same results were observed when the patients were categorized according to the indeterminate and symptomatic clinical forms. We conclude that the detection of the C4 component by ELISA is an efficient methodology to assess LP activation in serum from patients with chronic CD, enabling to differentiate the activation profile between patients and controls..